Increasing Trends in Soil Heat Extremes Following Flash Drought Outbreaks - Yangyang Jing; Shuo Wang; Pak Wai Chan; Zong‐Liang Yang (Geophysical Research Letters)
Abstract Flash droughts, characterized by rapid declines in soil moisture (SM), pose significant threats to ecosystems. Understanding the response of soil temperature (ST) to the rapid SM decline during flash droughts has critical implications for the root systems of terrestrial ecosystems. In this study, we identify soil heat extreme events that follow flash drought outbreaks. Our findings reveal that global land areas experience a significant increase in soil heat after the outbreak stage of flash droughts, with affected areas expanding by an average of 4.36%–9.74% per decade. Humid regions show a significantly higher percentage of affected land areas compared to arid regions. The proportion of soil heat extremes following flash drought outbreaks increases significantly by 16.53%–23.38%, with event days occurring twice as often, particularly in humid regions. This suggests that root systems will encounter exacerbated stress as soil heat intensifies during sudden abnormal soil drying.